Influence of lack of night sleep on the cognitive set by indicators of EEG rhythms coupling - Yakovenko Irina A.; Petrenko Nadejda E.; Cheremoushkin Evgeniy A.; Dorokhov Vladimir B.; Bakaeva Zarina B.; Yakunina Elena B.; Torshin Vladimir I.; Starshinov Yuri P.; Sveshnikov Dmitry S. (Социально-экологические технологии, 2020)
The aim of the study is investigation of nighttime sleep effect on the performance of a cognitive setting in terms of the coupling of EEG rhythms. The coupling of 5 rhythm: beta-1, beta-2, gamma, alpha and theta rhythms of EEG during the formation and testing of cognitive set was studied for 120 students (17 with short-term night sleep and 15 with a full night sleep). Multi-channel EEG was recorded. EEG evaluation was carried out by continuous wavelet transform based on the “mother” complex Morlet wavelet in the range of 1–35 Hz. Maps of the distribution of the values of the modulus of the wavelet transformation coefficient, which reflect amplitude changes of the potentials were analyzed. The Pearson correlation coefficient was a measure evaluating the coupling of EEG rhythms. The subjects with a short night’s sleep showed almost all of the relations of EEG rhythms (8 couples) during the formation stage of presentation. Students with a full night’s sleep showed statistically significant coupling of the following pairs of rhythms: alpha–beta-1, alpha–gamma and beta-2–gamma. Students with short-term night sleep demonstrated the 3 significant couples: alpha–beta-1, beta-1–gamma and beta-2–gamma during the testing stage. Well-slept students showed an increase in the number of connections (6 couples) in relation to the stage of formation of the set due to the addition of connections with the theta rhythm. The obtained data could indicate that the thalamo-cortical and cortico-hippocampal structural-functional associations work differently in the groups of subjects.